Poder legislativo, leis, democracia e saúde dos brasileiros - Penha Junior, Nilton Luiz da (2013)
The purpose of this study was to examine the sites of States Legislative Assemblies throughout Brazil in order to verify the transparency and effectiveness of the Legislature, evaluating bills, ordinary and complementary laws, comparing the number of laws in general versus oral health , drawing a parallel with the health of the population, as well as their regional differences. The methodology was exploratory, on the websites of the States Legislative Assemblies and the on Federal District. Observed: fewer laws on oral health in the Midwest Region of Brazil and more laws with dental concern in southern region, some sites do not provide the bills for consideration and policy of the population, as it was found that from the beginning to the closing of the search, the page of the Legislative Assembly of the State of Alagoas was not accessible to any public consultation and there are problems to check all bills on the site of Rio de Janeiro State, for that they, only submit the last 10 years (projects of bills) and page of Santa Catarina State, only shows up to the number 300, and there may be more laws and projects of bills, but the site does not allow visualization. We conclude that there is a need for standardization of domains and sites of the Legislature, as well as the computerization and daily update of legislative activities is not available for public consultation of voters, which strengthens democracy and provides recovery of the population. There may be transfer relevants states legislatives informations, regional laws may contribute to the development of the others regions of Brazilian states and the Federal District .